What styles of reasoning are important in primary English?. Issue 4 (19th June 2021) - Oliver, Michaela
Abstract: The importance of teaching reasoning in schools is widely recognised. Yet this has presented teachers with difficulties, particularly in primary education. Difficulties partially stem from a lack of cohesive theory about reasoning for education and a lack of specificity about it in the English National Curriculum. One route to improved teaching of reasoning is through recognition of the importance and prevalence of discipline‐specific practices. This paper draws on socio‐cultural theory and disciplinary literacy research to argue that some reasoning practices are discipline specific. The theoretical lens of reasoning styles is adopted. A cognitive history approach has been used to create a framework of reasoning styles important in primary English. English represents a curriculum area that is currently poorly understood in terms of its prevalent reasoning practices. This paper, therefore, makes important theoretical and pedagogical contributions to existing research. Examples of student engagement with identified reasoning styles are provided. The framework and accompanying examples will help teachers to support the development of student reasoning, particularly in the subject of English. Developing students' meta‐awareness of patterns of language use is beneficial. Development may also support students to become fuller members of the English academic community.